Simulation Of Traveling Salesman Problem For Distribution Of Fruits In Bogor City With Simulated Annealing Method: Simulation Of Traveling Salesman Problem For Distribution Of Fruits In Bogor City With Simulated Annealing Method - Ali Khumaidi; Ridwan Raafi'udin; Indra Permana Solihin (Jurnal Mantik, 2020)
Traveling Salesman Problem (TSP) is a problem of finding the shortest distance when a salesman visits a number of cities, provided that each city is visited exactly once and then returns to the initial city. TSP simulations for fruit distribution in Bogor city with each location having x and y coordinates as distances. The TSP used is a symmetrical TSP whose distance from city a to b has the same distance as city b to a. To solve and find solutions to problems using the Simulated Annealing (SA) Algorithm. The working principle is that at high temperatures metal liquid particles have a high energy level so it is relatively easy to move against other particles. Then as the temperature drops the particle slowly adjusts itself to form a configuration so that a stable state with a minimum energy level is obtained. This minimum energy is the shortest distance. Based on experiments that have been done using SA Algorithm on the TSP problem, the results show that the number of iterations that produce the optimal solution depends on the number of simulated locations. The more simulated location points, a large number of iterations are needed.